Urocaridella arabianensis n. sp., a new Palaemonid shrimp (Crustacea, Decapoda, Palaemonidae) from Lakshadweep Islands, India with taxonomic comparison on the genus Urocaridella Borradaile, 1915 - Akash, S.; Purushothaman, P.; Madhavan, Manu; Ravi, Charan; Hisham, T. Jafer; Sudhakar, M.; Kumar, T.t. Ajith; Kuldeep, Lal K (Zootaxa, 2020)
A new species of the genus Urocaridella Borradaile, 1915, Urocaridella arabianensis n. sp. is described and illustrated based on fifty-five specimens collected from the reef regions of Agatti Island, Lakshadweep, Arabian Sea. Urocaridella arabianensis n. sp. is morphologically close to U. pulchella Yokes & Galil, 2006, reported from the Mediterranean Sea. However, the present specimen is clearly distinguished with its rostrum length, which is 1.7 to 2.1 times as long as carapace, 10 ventral rostral teeth, carpus of 1st pereopod is 2.5 times long as palm, carpus of 2nd pereopod is 1.8 times as long as palm, presence of a spine in latero-middle of the fourth and fifth abdomens and the sixth abdominal segment is 2.3 times long as the fifth segment. Partial segment of the mitochondrial COI, 16S rRNA and nuclear gene 18S rRNA and H3 indicates that the new species is sister to a clade comprising of U. pulchella, U. antonbruunii and U. degravei. The pair wise genetic distance of COI showed great distance with the closest congeneric species.